The Potential Effects of Quercetin-Loaded Nanoliposomes on Amoxicillin/Clavulanate-Induced Hepatic Damage: Targeting the SIRT1/Nrf2/NF-κB Signaling Pathway and Microbiota Modulation - Mahran Mohamed Abd El-Emam; Mahmoud Mostafa; Amina A. Farag; Heba S. Youssef; Azza S. El-Demerdash; Heba Bayoumi; Mohammed A. Gebba; Sawsan M. El-Halawani; Abdulrahman M. Saleh; Amira M. Badr; Shorouk El Sayed (MDPI AG, 2023)
Amoxicillin/clavulanate (Co-Amox), a commonly used antibiotic for the treatment of bacterial infections, has been associated with drug-induced liver damage. Quercetin (QR), a naturally occurring flavonoid with pleiotropic biological activities, has poor water solubility and low bioavailability. The objective of this work was to produce a more bioavailable formulation of QR (liposomes) and to determine the effect of its intraperitoneal pretreatment on the amelioration of Co-Amox-induced liver damage in male rats. Four groups of rats were defined: control, QR liposomes (QR-lipo), Co-Amox, and Co-Amox and QR-lipo. Liver injury severity in rats was evaluated for all groups through measurement of serum liver enzymes, liver antioxidant status, proinflammatory mediators, and microbiota modulation. The results revealed that QR-lipo reduced the severity of Co-Amox-induced hepatic damage in rats, as indicated by a reduction in serum liver enzymes and total liver antioxidant capacity. In addition, QR-lipo upregulated antioxidant transcription factors SIRT1 and Nrf2 and downregulated liver proinflammatory signatures, including IL-6, IL-1β, TNF-α, NF-κB, and iNOS, with upregulation in the anti-inflammatory one, IL10. QR-lipo also prevented Co-Amox-induced gut dysbiosis by favoring the colonization of Lactobacillus, Bifidobacterium, and Bacteroides over Clostridium and Enterobacteriaceae. These results suggested that QR-lipo ameliorates Co-Amox-induced liver damage by targeting SIRT1/Nrf2/NF-κB and modulating the microbiota.